Ethnic school segregation in England: measurement, change and prediction - Mitchell, PM (2022)
As England becomes increasingly ethnically diverse there have been concerns over perceived ethnic divisions within society (Cantle, 2013; Casey, 2016; May, 2016). Schools have been a focal point for these discussions, and the government is now committed to ensuring state schools become places where students create “relationships with others from different ethnic... groups” (HM Government, 2018a, p. 26).